Democracy in the Framework of Shura: A Conceptual Study of Contemporary Muslim Intellectual Thought - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
The article highlights the intellectual response of contemporary Muslims on the philosophical construct and relational concept of democracy and shura. This was traced from selected writings of its advocates that discussed philosophical and epistemological background and current democratic situation in the Muslim countries and its fundamental relations with Islamic political aspiration and its historical manifestation and scientific backdrop. The intellectual debate pertinent to the idea of democracy and its compatibility with Islamic principles were rigorously developed by Muslim activists and democrats represented by Rachid Ghannouchi, Ahmad Raysuni, Fazlur Rahman, Anwar Ibrahim, Siddiq Fadzil, Nurcholish Madjid, Mustafa Akyol, and etcetera. The study is based on qualitative approaches using descriptive and analytical technique. The finding shows the dynamic force of ideas formulated on the theoretical framework of democracy reinforced with textual evidence and in line with Islamic political principles (siyasah syariyyah) and its universal ummatic ideal (pax-Islamica). Its underlying structure was built upon universal ethical values that formed the basis of state ideology. It positively embraces its values and ideals projected in the context of nation-state, which uphold sublime vision toward shaping a sustainable, just and liberal order. Its approaches were in line with the principle of shura and constitutional ideas aiming to safeguard fundamental aspiration of the people and their legitimate right and interest and their collective voice.